QUYOSH KONSENTRATORLARI (Лучшие интеллектуальные исследования, 2025)
Abstract: Today, the demand for electric energy is increasing, and traditional fuels are not inexhaustible. That is why we are trying to find different ways to get electricity from renewable energy sources. One of these methods is to obtain electricity through solar concentrators. Using theoretical data, we can see the possibilities of obtaining electricity from solar concentrators.